2021
DOI: 10.3390/jcm10225440
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics, Complications and Outcomes of Patients with Severe Acute Respiratory Distress Syndrome Related to COVID-19 or Influenza Requiring Extracorporeal Membrane Oxygenation—A Retrospective Cohort Study

Abstract: Extracorporeal membrane oxygenation (ECMO) represents a viable therapy option for patients with refractory acute respiratory distress syndrome (ARDS). Currently, veno-venous (vv) ECMO is frequently used in patients suffering from coronavirus disease 2019 (COVID-19). VV-ECMO was also frequently utilised during the influenza pandemic and experience with this complex and invasive treatment has increased worldwide since. However, data on comparison of clinical characteristics and outcome of patients with COVID-19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…In our study, no differences were found in 28- and 60-day mortality between COVID-19–associated ARDS and non-COVID-19 ARDS, both unadjusted as adjusted for confounders. This is supported by previous studies showing equal survival at different time points ( 13 , 14 , 23 , 29 ). A recent study by Fanelli et al ( 23 ) found, when comparing patients receiving ECMO for either Influenza A H1N1 or COVID-19 ARDS, that 60-day mortality was only in the disadvantage of COVID-19 when unadjusted for confounders.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our study, no differences were found in 28- and 60-day mortality between COVID-19–associated ARDS and non-COVID-19 ARDS, both unadjusted as adjusted for confounders. This is supported by previous studies showing equal survival at different time points ( 13 , 14 , 23 , 29 ). A recent study by Fanelli et al ( 23 ) found, when comparing patients receiving ECMO for either Influenza A H1N1 or COVID-19 ARDS, that 60-day mortality was only in the disadvantage of COVID-19 when unadjusted for confounders.…”
Section: Discussionsupporting
confidence: 89%
“…These differences may even be more important in the critically ill receiving VV ECMO. Although previous studies did not find differences in survival between patients receiving ECMO for COVID and non-COVID-ARDS, those studies are often small and correction for confounders is limited (13–15). Second, a change in patient outcomes over time in 2020 was found by different study groups, showing an increase in mortality in the second wave (16, 17).…”
mentioning
confidence: 94%
“…Few studies have directly compared mortality and complication rates for patients supported with ECMO for the management of COVID-19-related ARDS versus non-COVID-19-related viral ARDS. Studies with such direct comparisons have used small sample sizes and reached varying conclusions (7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%
“…Compared to ARDS of other etiology COVID-19 patients with ECMO support stay longer on ICU 6 . Increased length of ICU stay and mortality are worrying, especially in the pre-vaccination era.…”
Section: Introductionmentioning
confidence: 99%